Multifunctional Use of Agricultural Land with Support for Selected Ecosystem Services in the Territory Protected Water Management Area Žitný Ostrov - Zdena Krnáčová; Pavol Kenderessy; Zuzana Baránková; Mária Barančoková; Martin Labuda (Land, 2023)
Agroecosystems represent one of the largest managed systems in the world and are also considered to be the largest surface polluters. This is particularly evident in highly vulnerable areas such as the model area assessed in our study, the Protected Water Management Area Žitný Ostrov, which contains the most productive soils in the Slovak Republic. At the same time, the Žitný Ostrov represents the largest groundwater reserves in Central Europe. We based this study on the information system of valued soil ecological units (VSEUs) and their spatial extension to the agricultural soils of Slovakia. We used the synthetic–parametric method for a summary (aggregated) evaluation of the production potential of provisioning soil services, which we have classified into 10 categories (1—very low potential; 10—very high potential). Overall, there were 3000 individual VSEUs identified in the area of interest. By eliminating repetitive VSEUs, we evaluated 72 subtypes and, based on similarity parameters, they were further aggregated into 40 soil subtypes. The result is a spatial representation of the proposed zones within the model area (zones for sustainable economic use of soils with the support for ecologization of agricultural technologies, non-productive land use, cultural and social development of rural areas, and the protection and revitalization of the landscape and its components). The approach is also suitable for use in other areas.